Acerca de la formación del Puente-istmo Centroamericano Neridional, con énfasis en el desarrollo acaecido desde el Campaniense al Eoceno - Seyfried, Hartmut (2011)
The southern part of the Central American isthmus resulted from the subduc-tion of the oceanic Pacific plate beneath the oceanic Caribbean plate. The rise of this land-bridge from the pre-Campanian ocean floor is characterized by a Campanian to Eocene island arc stage, an Oligocene to Miocene swell stage as well as a Pliocene to Recent mountain chain stage. The present study deals main-ly with the island arc stage. The first island arcs emerged towards the begin-ning of the Late Campanian: a non-volcanic archipelagos of basaltic islands bounded by strike-slip fault scarps. Where insular shelves did exist, they were colonized by rndist biostromes; the talus originated mainly by rock-falling and avalanching. As early as at the end of the Late Campanian, the greater part of this basaltic archipelagos subsided. During the Paleocene and the Eocene, it be-came more or less deeply buried under hemipelagic sediments deriving from the active andesitic island arc which formed at the site of the actual mainland. The borders of this andesitic island arc were oversupplied with clastics'due to excessive erosion. Thus, carbonate shelveo could hardly extend and were restric-ted to some patchy areas where communities of larger foraminifera and red algae developped during the Middle-Upper Eocene. Due to local uplift, however, a rela-tively small isolated Bahama-type carbonate platform established in the western Bajo Tempisque area, producing the (probably Eocene) Barra Honda formation. This carbonate platfrom both supplied slide blocks to the adjacent basins and was surged up and by-passed by turbidites deriving from the andesitic island arc. Paleovertebratological data evidence that from both island chains only the Cam-panian one permitted an exchange of terrestrial animals between North and South America. This early connection must have been disrupted, from the latest Campa-nian onward, by transform displacements and/or plate rotations. In this context it may be annotated that the present-day geological configuration in the Costa Rican area provides only incomplete paleogeographical profiles. A hypothetical section fitting the Peninsula de Nicoya and Bajo Tempisque area with the Quepos — File Costae — Talamanca area would join the missing links. This configura-tion, however, requires NW-SE lateral displacements which, at the moment, can neither be localized nor be proved due to the lack of paleomagnetical data.